2016
DOI: 10.1302/0301-620x.98b11.34693
|View full text |Cite
|
Sign up to set email alerts
|

The use of high-dose dual-impregnated antibiotic-laden cement with hemiarthroplasty for the treatment of a fracture of the hip

Abstract: AimsA fracture of the hip is the most common serious orthopaedic injury, and surgical site infection (SSI) is one of the most significant complications, resulting in increased mortality, prolonged hospital stay and often the need for further surgery. Our aim was to determine whether high dose dual antibiotic impregnated bone cement decreases the rate of infection.Patients and MethodsA quasi-randomised study of 848 patients with an intracapsular fracture of the hip was conducted in one large teaching hospital o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 43 publications
2
47
0
1
Order By: Relevance
“…This period includes patients recruited into the quasi-randomised controlled trial. 6 This trial ran from April 2008 to May 2012 and randomised patients to receive LDSAC or HDDAC for their hip hemiarthroplasty. Following completion of the trial the trust switched to HDDAC as the standard of care for hip hemiarthroplasty.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This period includes patients recruited into the quasi-randomised controlled trial. 6 This trial ran from April 2008 to May 2012 and randomised patients to receive LDSAC or HDDAC for their hip hemiarthroplasty. Following completion of the trial the trust switched to HDDAC as the standard of care for hip hemiarthroplasty.…”
Section: Methodsmentioning
confidence: 99%
“… 5 A quasi-randomised controlled trial conducted by Sprowson et al recently demonstrated that high dose dual-antibiotic cement (HDDAC) (Copal G+C, Heraeus Medical, UK) reduces rates of deep SSI when compared to the standard low dose single-antibiotic cement (LDSAC) (Palacos R+G, Heraeus Medical, UK). 6 Palacos R+G contains 0.5 grams of gentamicin whilst Copal G+C contains 1 gram of gentamicin and 1 gram of clindamycin per mix. The addition of clindamycin to gentamicin-loaded bone cement is known to work synergistically to yield higher antibiotic release in vivo as well as providing a wider antibiotic coverage.…”
Section: Introductionmentioning
confidence: 99%
“…To decrease postoperative deep infection, preventive care, including drainage and the administration of prophylactic antibiotics, is needed after bone tumor surgeries. Recently, several new techniques, including antibiotic-impregnated cement and an implant with silver coating or iodine coating, have been used to prevent deep infection after orthopaedic surgery [ 31 34 ]. More efforts should be made to decrease postoperative deep infection in patients with a high risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…There was 1 level I study comparing single antibiotics to dual antibiotics in ALC (Table 1). Sprowson et al [10] performed a quasirandomized controlled trial treating 848 hip fracture patients with cemented hemiarthroplasty, randomizing patients to receive either low-dose single antibiotic impregnated or high-dose dual antibiotic impregnated cement. There were 448 patients who received single antibiotic cement mixed with 0.5 g of gentamicin and 400 patients who received dual antibiotic cement mixed with 1 g of clindamycin and 1 g of gentamicin.…”
Section: Level I Studiesmentioning
confidence: 99%
“…The mechanism behind this effect may be due to "passive opportunism," where the second antibiotic appears to act as a soluble passive additive, increasing the porosity and available surface area for elution [8]. The advantage of enhanced elution is the ability to maintain intra-articular antibiotic concentrations above the minimal inhibitory concentration for a longer period of time, thereby preventing polymicrobial pathogen colonization [6,10,11]. However, several concerns have been raised regarding antibiotic utilization in ALCs.…”
mentioning
confidence: 99%